Clitic in Meto Language - Radja, Markus Dimu; Langkameng, Oce Antipas; Mau, Hendrik (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2022)
This writing deals with Analysis of Clitic in Meto Language. The aims of this writing are to identify forms of clitic in Amanatun dialect and determined the meaning of each form of clitic in Amanatun dialect. Due the topic discussed; this writing is conducted by using descriptive method. To obtain the data, the writer took the native speakers of Meto Language in Santian Village. In finding the data the writer took five informantas. In collecthing the data, the writer used questionnaire as the instrument. The result, of the writing concluded that the clitic on Amanatun dialect of Meto Language, consist of two parts: Proclitic and Enclitic. Proclitic covering [m-], [n-] and [t-]. Enclitic [-kuk], [-kum] and [-kun].